Pengaruh Faktor Politik dalam Pengungkapan Transparansi Informasi Website Pemerintah Daerah: Studi Empiris Kabupaten/Kota Pulau Jawa dan Bali Periode 2017-2020 - Mega Mistika; Deviani Deviani (Universitas Negeri Padang, 2023)
This research aims to determine the effect of political factors such as political strength and political competition level on transparency information of local government websites in Java and Bali. The sampling techniques used was purpose sampling with a total of 122 local government websites using multiple linear regression with the help of IBM SPSS 23 software. This result shows that political strength and political competition level does not affect the transparency of local government. There is no effect on transparency when the pressure from public and political party were high. In addition, people must remain wary of information from local government to hold them accountable.